Augmentation of Nanofluids Heat Transfer in a Circular Pipe with Coiled Tube Insert as Heat Source and Swirl Generator - D. Salman, S.; ., . (International Journal of Engineering and Technology, 2019)
This research present steady state heat transfer and fluid flow characteristics in concentric pipe with coiled tube insert for turbulent flow regime with metal oxide nanofluid using ANSYS-FLUENT 18.0 where the governing equations of mass, momentum and heat transfer were solved simultaneously, using the k-e two equations turbulence model. Copper was chosen as the as metal for the construction of pipe and the helical tube insert. Coiled tube with curvature to pitch ratio as 1 and 2.5 mm in diameter with 1% volume fractions of TiO2 and CuO Nanofluid with Reynolds number ranged from 4000-16000 were considered in this research. The heat generated from constant water temperature (80 Â°C) with constant flow rates in helical coil (Re=4000). The Result shows that the heat and friction coefficients conducted by vortex generator raised with Reynolds number and accretion of nanoparticle presence. Furthermore, the maximum rate of heat transfer with significant intension in friction coefficient has been produced TiO2 nanofluid by as compared with CuO and water.Â Â